11 Inclusive palliative care teaching: diversifying the representation of patients in undergraduate medical education. (14th March 2023) - Brodrick, Robert; Cherfils, Mildrade; Price, Annabel; Spathis, Anna; Barclay, Stephen
Abstract : Background: Ethnically diverse groups are underrepresented in undergraduate medical education in the UK. Students prefer more inclusive patient representation during teaching. In alignment with our university's commitment to address health inequalities, we wished to represent more ethnic diversity within the palliative medicine curriculum. Methods: We co-designed a video-based teaching session with a subject matter expert with lived experience of Ibibio Nigerian culture. The explicit learning objectives focused on symptom management in liver failure with alcohol withdrawal, best interests decision-making, palliative discharge planning, and controlled drug prescription practice. The implicit learning objectives included the influence of a simulated patient's cultural background and relationships. Three professional actors played the patient's partner, brother, and mother. The actors were filmed expressing complementary and divergent perspectives. Care was taken to avoid unhelpful tropes, stereotype perpetuation, or difference minimisation. Students were shown three video montages during the 90-minute session. The characters explored religious faith, existentialism, familial shame, stigmatisation of alcohol-dependence, miraculous healing, safeguarding concerns, and traditional Nigerian medicine. Jaundice with darker skin tone was demonstrated. An interactive group work format was chosen to help examine unconscious bias that might otherwise influence decision-making, complemented by anonymised polling software to encourage participation. Results: A total of 568 final year students have participated to date, of which 217 offered written feedback (38%). On a Likert scale of 1 to 5, with 5 being the most educationally useful, the median rating was 4.7 (range 3 to 5). Of surveyed students, 94% (204) expressed a wish for more teaching in this video-based format. Free text comments were extremely positive, including favourable reference to the session's central focus on a patient with Nigerian heritage. Conclusion: Creating videos for teaching purposes can increase student exposure to minoritised groups. Such intentional diversification of patient portrayal can be educationally useful and is well received.